Learning efficacy and user acceptance of a game-based social skills learning environment - Tan, Jean Lee (2013)
Social maladjustment places children at risk in early life as they are integral to many emotional, behavioral and psychological problems. If left untreated, these negative consequences may be precursors of serious problems in adulthood such as adult psychopathology and criminality. The possible deleterious effects of social skills deficits have underscored the importance placed on social skills programs in schools. To address the issue of acquisition of social skills, a Web-based game, as a specific instantiation of educational games for social skills training in a classroom setting was developed for this research. The game, Socialdrome® is aimed to intentionally teach children to identify and manage feelings, exercise self-control, solve social problems and negotiate conflict situations. Specifically, the research seeks to design and evaluate the game based on instructional and game design principles and investigate the learning efficacy and user acceptance that the children derive from the game-based learning environment, Socialdrome®.